Grafting of Thompson Seedless Scions onto Hardwood Cuttings of Three Grapevine Cultivars - Shabaq. M. Nafea. Hawezy (Zanco Journal of Pure and Applied Sciences, 2023)
In this study scion of Thompson seedless grape cultivar was grafted on three local grape cultivars (Chav-ga, Rash-meri and Tre-rash) rootstock by wedge grafting in 2021-2022, grafting were made manually on the 15th of Febrywary by using one-year old cuttings ( scion and rootstock). Growth parameters such as shoot length and diameter, dry weight of vegetative growth, number of leaves and leaves dry weight showed the significant difference while chlorophyll content showed non-significant difference among the cultivars. Generally Thompson seedless grafted on Rash-meri rootstock gave better results for most of the growth parameters in both seasons, while grade of callus, rate of graft take, root percentage and root numbers showed significant difference among the cultivars in both two seasons. However, root length showed non-significant difference between all cultivars, more over in Chav-ga cultivar it showed significant difference in root shoot ratio compared with another two cultivars. Grad of callus was higher (1.95 and 1.99) in Rash-meri and lower was (1.75 and 1.78) in Chav-ga. Rate of graft take was also higher when Thompson seedless grafted on Tre-rash cultivar (88.13 and 89.00 %) and (74.52 and 75.80 %) in Chav-ga rootstock for two experimental seasons respectively.